The Effects of Corporate Social Responsibility to the Corporate Value - Dwi Ermayanti Susilo (Arthatama: Journal of Business Management and Accounting, 2018)
This study aims to determine the influence of Corporate Social Responsibility to the company value. The research used quantitative method, which is conducted through data collection with secondary data from Indonesia Stock Exchange. While the population of all plastic and packaging sub-sector of manufacturing companies listed on Indonesia Stock Exchange which are as many as 14 companies, the sample fulfilled the criteria used in this research is 12 companies of plastic and packaging manufacturing company listed on Indonesia Stock Exchange from 2013 until 2017. Data analysis was conducted by using simple linear regression statistic method and hypothesis testing with t test. The results indicate that Corporate Social Responsibility have a positive effect to the corporate values of manufacturing company which is classified in manufacturing plastic and packaging sub-sector listed on Indonesia Stock Exchange. Practical and theoretical implications were also discussed.